Uptake-leak balance of SR Ca2+ determines arrhythmogenic potential of RyR2R420Q+/− cardiomyocytes. (September 2022) - Lopez, Ruben; Janicek, Radoslav; Fernandez-Tenorio, Miguel; Courtehoux, Marianne; Matas, Lluis; Gerbaud, Pascale; Gomez, Ana M.; Egger, Marcel; Niggli, Ernst
Abstract: Mutations of the RyR2 are channelopathies that can predispose to life threatening catecholaminergic polymorphic ventricular tachycardias (CPVTs) during exercise or stress. However, the cellular and molecular mechanisms that are causal for the arrhythmias downstream of the β-adrenergic receptor (β-AR) activation are not defined. They may be specific and different for each particular RyR2 mutation. Obvious possibilities are the phosphorylation of the mutated RyR2s or the stimulation of the SR Ca 2+ pump (SERCA), which could increase SR Ca 2+ loading. Potentially arrhythmogenic Ca 2+ signals, such as Ca 2+ waves, were recorded and analyzed from WT and RyR2 R420Q+/− mouse cardiomyocytes with confocal microscopy after field stimulation at 1 Hz. In RyR2 R420Q+/− cardiomyocytes we found a higher occurrence and frequency of Ca 2+ waves, particularly upon β-AR stimulation with isoproterenol. This was accompanied by a shorter latency to the first spontaneous wave. Wave velocity from raw traces, as well as amplitude and decay time constant (τ) analyzed in de-skewed traces were comparable in both cell types. To obtain further insight into the role of the SERCA we selectively stimulated SERCA in permeabilized myocytes using Fab fragments of a PLB antibody (2D12). Surprisingly, SERCA stimulation alone resulted in considerably higher wave frequencies than when mimicking β-AR stimulation with cAMP, particularly in RyR2 R420Q+/− cardiomyocytes. This may be a consequence of some protective SR Ca 2+ unloading resulting from the SR Ca 2+ leak via phosphorylated RyR2s in cAMP. Spark-to-spark recovery analysis suggested a remarkably higher Ca 2+ release sensitivity in RyR2 R420Q+/− cells, both in control and upon β-AR stimulation. Together these findings suggest that the fine balance between SR Ca 2+ loading via SERCA and the Ca 2+ leak via mutated and phosphorylated RyR2s is an important determinant for the overall cellular arrhythmogenicity prevailing in the RyR2 R420Q+/− myocytes. Graphical abstract: Unlabelled Image Highlights: Molecular mechanism(s) precipitating arrhythmias in RyR2 mutations are not defined. Both, SERCA stimulation and RyR2 phosphorylation during stress are possibilities. Ca waves were analyzed in myocytes of a transgenic RyR2 R420Q mouse by confocal imaging. Selective SERCA stimulation provoked more Ca waves than with RyR2 phosphorylation combined. The SR Ca leak after RyR2 phosphorylation may reduce Ca load and be antiarrhythmic.